New employer payroll taxes and entrepreneurship - Audrey Guo; Melanie Wallskog (W.E. Upjohn Institute for Employment Research, 2024)
How costly are taxes for young firms? In this paper, we demonstrate that even small payroll taxes significantly distort entry, growth, and hiring decisions. First, leveraging cross-sectional variation in the taxes faced by new employers, we find that higher taxes discourage new firms from hiring their first workers, with an elasticity of the number of new employers to taxes of -0.1. Second, studying changes in taxes after entry, we find that higher taxes lead more firms to exit, while also reducing employment for those who survive and leading some firms to avoid taxes by using non-taxable contract labor.
Keywords: H25; H71; L26; M13; 330; firm entry; young firms; labor costs; unemployment insurance